What are the predictors of heart failure in patients admitted with acute coronary syndrome? Data from a large national registry. (14th October 2021) - Timoteo, A; Aguiar Rosa, S; Mano, T; Cruz Ferreira, R; ,
Abstract: Background: Heart failure (HF) is a serious and frequent complication of acute myocardial infarction with important impact in outcome. Early treatment according to contemporaneous guidelines is essential to avoid that complication. Previous ischemic heart disease and HF are important predictors. Our objective is to identify additional predictors of HF in patients admitted with acute coronary syndrome (ACS). Methods: Analysis of all consecutive patients prospectively included in a large national registry of ACS. Patients with a previous history of ACS, myocardial revascularization or heart failure were excluded from the analysis. The group that developed HF was compared with the group without HF and multivariate logistic regression analysis was performed to identify independent predictors of HF during hospitalization (Killip class >1). Results: A total of 19, 248 patients were included, and 17.3% developed HF during hospitalization. Patients with HF were older, less often males and smokers, and more often with hypertension and diabetes, as well as other comorbidities (p<0.001). ST elevation myocardial infarction (STEMI), atrial fibrillation, mechanical and electrical complications are also more frequent. Patients that developed HF have higher in-hospital mortality (0.9% vs. 12.1%). Independent predictors of HF are female gender (OR 1.64, 95% CI 1.15–2.33), age (1.42, 1.25–1.62, per 10-year increase) diabetes (1.97, 1.44–2.69), atrial fibrillation (2.65, 1.66–4.23), STEMI (2.30, 1.70–3.10), multivessel disease (1.52, 1.13–2.05) and initial admission in a hospital without catheterization laboratory as a protective factor (0.71, 0.52–0.96). In STEMI patients, anterior location is also an independent predictor. Conclusions: In patients admitted with a first ACS and without previous ischemic heart disease or heart failure, female gender, increasing age, diabetes, atrial fibrillation, STEMI and multivessel disease are the main predictors of worst outcome and these patients should be treated more aggressively to avoid HF development. Funding Acknowledgement: Type of funding sources: None.